Medical Isotopes - Ali Raza Naqvi, Syed; Babar Imrani, Muhammad (IntechOpen, 2021)
Radioisotopes are widely used in the medical field for imaging and therapy of diseases by themselves or by tagging with other molecules that have the potential to target diseased cells. In imaging protocol, the radioisotope, such as technetium-99m or indium-111, decays through ?-radiation emissions, which are located by a scintigraphic camera (SPECT or PET) in the form of 2/3D image formation of the diseased organ. The other kind of radioisotopes, such as Lutetium-177 or Actinium-225, are those that decay through ?/?-decay, which is due to its valuable linear energy transfer that is in clinical use to eliminate diseased cells. This book will cover valuable information about selected diagnostic and therapeutic radioisotopes along with localization mechanisms of radioisotopes directly or through nanoparticles at diseased cells.